A Higher Abundance of O-Linked Glycans Confers a Selective Advantage to High Fertile Buffalo Spermatozoa for Immune-Evasion From Neutrophils - Batra, Vipul; Dagar, Komal; Nayak, Samiksha; Kumaresan, Arumugam; Kumar, Rakesh; Datta, Tirtha K. (Frontiers in Immunology, 2020)
The glycans on the plasma membrane of cells manifest as the glycocalyx, which serves as an information-rich frontier that is directly in contact with its immediate milieu. The glycoconjugates (GCs) that adorn most of the mammalian cells are also abundant in gametes, especially the spermatozoa where they perform unique reproduction-specific functions e.g. inter-cellular recognition and communication. This study aimed to implicate the sperm glycosylation pattern as one of the factors responsible for low conception rates observed in buffalo bulls. We hypothesized that a differential abundance of glycans exists on the spermatozoa from bulls of contrasting fertilizing abilities endowing them with differential immune evasion abilities. Therefore, we investigated the role of glycan abundance in the phagocytosis and NETosis rates exhibited by female neutrophils (PMNs) upon exposure to such spermatozoa. Our results indicated that the spermatozoa from high fertile (HF) bulls possessed a higher abundance of O-linked glycans e.g. galactosyl (β-1,3)N-acetylgalactosamine and N-linked glycans like [GlcNAc]1-3, N-acetylglucosamine than the low fertile (LF) bull spermatozoa. This differential glycomic endowment appeared to affect the spermiophagy and NETosis rates exhibited by the female neutrophil cells (PMNs). The mean percentage of phagocytizing PMNs was significantly different (P<0.001) for HF and LF bulls, 28.44% and 59.59%, respectively. Furthermore, any introduced perturbations in the inherent sperm glycan arrangements promoted phagocytosis by PMNs. For example, after in vitro capacitation the mean phagocytosis rate (MPR) rate in spermatozoa from HF bulls significantly increased to 66.49% (P<0.01). Besides, the MPR increased to 70.63% (p<0.01) after O-glycosidase & α2-3,6,8,9 Neuraminidase A treatment of spermatozoa from HF bulls. Moreover, the percentage of PMNs forming neutrophil extracellular traps (NETs) was significantly higher, 41.47% when exposed to spermatozoa from LF bulls vis-à-vis the spermatozoa from HF bulls, 15.46% (P<0.001). This is a pioneer report specifically demonstrating the role of O-linked glycans in the immune responses mounted against spermatozoa. Nevertheless, further studies are warranted to provide the measures to diagnose the sub-fertile phenotype thus preventing the losses incurred by incorrect selection of morphologically normal sperm in the AI/IVF reproduction techniques.